CreER(T2) expression from within the c-Kit gene locus allows efficient inducible gene targeting in and ablation of mast cells - Heger, Klaus; Seidler, Barbara; Vahl, J. Christoph; Schwartz, Christian; Kober, Maike; Klein, Sabine; Vöhringer, David; Saur, Dieter; Schmidt-Supprian, Marc (European Journal of Immunology, 2014)
Mast cells are abundantly situated at contact sites between the body and its environment, such as the skin and, especially during certain immune responses, at mucosal surfaces. They mediate allergic reactions and degrade toxins as well as venoms. However, their roles during innate and adaptive immune responses remain controversial and it is likely that major functions remain to be discovered. Recent developments in mast cell-specific conditional gene targeting in the mouse promise to enhance our understanding of these fascinating cells. To complete the genetic toolbox to study mast cell development, homeostasis and function, it is imperative to inducibly manipulate their gene expression. Here, we report the generation of a novel knock-in mouse line expressing a tamoxifen-inducible version of the Cre recombinase from within the endogenous c-Kit locus. We demonstrate highly efficient and specific inducible expression of a fluorescent reporter protein in mast cells both in vivo and in vitro. Furthermore, induction of diphtheria toxin A expression allowed selective and efficient ablation of mast cells at various anatomical locations, while other hematopoietic cells remain unaffected. This novel mouse strain will hence be very valuable to study mast cell homeostasis and how specific genes influence their functions in physiology and pathology.
EVALuna2:25867